A realização do exame Papanicolaou em Paracatu-MG: análise do período 2004 a 2006 - Arantes, Rosalba Cassuci (2009)
In the present research was realized a descriptive and retrospective study having as source of the data the Requisition Sheets of Cytopathologic Tests of the National Program for Cancer of the Cervix Control (PNCCCU) of the Unified Health System in Paracatu - MG of women from 25 to 59 years old, from 2004 to 2006, order identify the coverage of the implementation of the Pap Test and compare it with the registered data in the Cervical Cancer Data System (SISCOLO), identify the number of women who submit more than once to the test and describe their results. The study identified a discrepancy between SISCOLO information about the number of realized tests and the number of women who have done was in the order of 15%. The Pap test coverage is not the ideal, since than just 50% of women have access to the exam and among those who do the test 42.51% are in the age group of less risk for the disease. The identification of precursor lesions of cervical cancer allowed a detection rate of 0.73%, lower than found in other studies. Another data was clarified in this study, 18,58% of women with abnormal results in epithelial cells do not have doctor accompaniment. According to several authors the effectiveness in controlling cervical cancer depends on high quality levels, coverage and monitoring of women with lesions identified. This study suggest the necessity of reorganization of cervical cancer control in Paracatu, increasing its coverage, the active search of the population at greater risk and the accompaniment of the suggested cases, according to the recommendations of PNCCCU. It should also be considered the interdependence relationship between health-promotion actions for cancer prevention, detaching the need of control at local level, of the samples, accompaniment of the examined women and adapting strategies to raise awareness of women under risk to the realization of the Pap test.